2001
DOI: 10.1080/713601083
|View full text |Cite
|
Sign up to set email alerts
|

Aid and Performance: A Reassessment

Abstract: Two visions of aid effectiveness and allocation are compared. The first, corresponding to the new aid paradigm, argues that aid is only effective if domestic policies are appropriate. The second, in contrast, argues that aid effectiveness depends on the external and climatic environment: the worse this environment, or the more vulnerable the recipient countries, the greater the effectiveness of aid. Cross-sectional econometric tests related to GDP growth on two 12-year pooled periods clearly favour the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
1
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(227 citation statements)
references
References 20 publications
8
204
1
14
Order By: Relevance
“…Another interpretation, or perhaps qualification, is that other factors undermined the effectiveness of aid in the poor performing countries. One potential source might be exogenous shocks; Guillaumont and Chauvet (2001) and Lensink and Morrissey (2000) show that external shocks and aid instability are growth-reducing although aid remains a positive factor. Our analysis cannot identify these (growth-retarding) factors, but it can suggest countries (and periods) that may warrant further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Another interpretation, or perhaps qualification, is that other factors undermined the effectiveness of aid in the poor performing countries. One potential source might be exogenous shocks; Guillaumont and Chauvet (2001) and Lensink and Morrissey (2000) show that external shocks and aid instability are growth-reducing although aid remains a positive factor. Our analysis cannot identify these (growth-retarding) factors, but it can suggest countries (and periods) that may warrant further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The Burnside and Dollar study has received abundant comments from scholars and policy makers (Guillaumont & Chauvet, 2001;Collier & Dehn, 2001;Easterly et al, 2003) with some claiming that corresponding findings are extremely data-dependent (Clemens et al, 2004). Whereas Clemens et al (2004) have established that aid is beneficial in the short-term; Minou and Reddy (2010) have recently found that the beneficial effect could also be in the long-term.…”
Section: Controversial Views In the Literaturementioning
confidence: 99%
“…Based on the observation that ODA does not influence the mean GDP growth rate, the scientific community has started to look for the necessary conditions for its effectiveness. While the work of Burnside and Dollar (2000), Hansen and Tarp (2001), Guillaumont and Chauvet (2001) showed that the relationship between aid and growth was influenced by factors such as institutions, the quality of governance or macroeconomic instability, other studies such as those of Hadjimichael et al (1995), Lensink and White (2001) indicate that due to the presence of non-constant returns to scale, the relative non-effectiveness of aid was due to inadequate amounts of disbursements. More recently and following the work of Clemens et al (2004) a new trend of research has emerged.…”
Section: Literature Reviewmentioning
confidence: 99%